Pseudophakic/ aphakic corneal edema – morphometric predisposing factors analysis based on the fellow eye examination - Woyna-Orlewicz, Anna; Wylęgała, Edward; Dobrowolski, Dariusz; Wróblewska-Czajka, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To find morphometric factors predisposing to the development of corneal decompensation following cataract surgery. Material and methods: Study group consisted of 50 patients after keratoplasty performed as pseudophakic/ aphakic corneal edema (PCE/ACE) treatment. Control group formed 50 patients after cataract removal without signs of corneal decompensation. Specific subgroups were analyzed too. The morphometric data of the fellow eye anterior chamber were obtained with Visante OCTTM. Results: Anterior chamber depth and anterior chamber angle width were significantly smaller in study group (p<0.00001, U-test). With excluded preoperative risk factors: Fuchs dystrophy, acute angle closure glaucoma attack history the significant differences were also observed (p<0.01). In Fuchs’ dystrophy and intraoperative complication subgroups comparison these two anterior chamber parameters were smaller too (p<0.001). Anterior chamber width was also smaller in study group with p = 0.001. Central corneal thickness was higher in study group with p = 0.013. After exclusion of patients with Fuchs’ dystrophy there was no difference in comparison (p = 0.34). The difference in total axial length comparison was insignificant (p = 0.18). Relative anterior microphthalmos was diagnosed in 31 patients of study group (62%) and in 17 of control (34%). Conclusions: Small anterior chamber dimensions and higher central corneal thickness due to Fuchs’ dystrophy are factors influencing the risk of PCE/ACE development.